2015
DOI: 10.1589/jpts.27.1129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of revised high-heeled shoes on foot pressure and static balance during standing

Abstract: [Purpose] The purpose of this study was to investigate the effects of revised high-heeled shoes on the foot pressure ratio and static balance during standing. [Subjects and Methods] A single-subject design was used, 15 healthy women wearing revised high-heeled shoes and general high-heeled shoes in a random order. The foot pressure ratio and static balance scores during standing were measured using a SpaceBalance 3D system. [Results] Forefoot and rearfoot pressures were significantly different between the 2 ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…In the opinion of Bae et al, revised high-heeled shoes (by making use of tunnel technology with excellent shock absorption and a rearward decrease in the wedge angle) produce significantly higher rearfoot pressure and lower forefoot pressure and have a greater positive effect than standard high-heeled shoes on static balance [2].…”
Section: Discussionmentioning
confidence: 99%
“…In the opinion of Bae et al, revised high-heeled shoes (by making use of tunnel technology with excellent shock absorption and a rearward decrease in the wedge angle) produce significantly higher rearfoot pressure and lower forefoot pressure and have a greater positive effect than standard high-heeled shoes on static balance [2].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that most of the participants commented that the revised HHSs successfully supported the arch of the foot, compared with the standard HHSs, while standing. Preliminary data of 15 healthy adult women have shown that revised HHSs produce a 10% weight shift to the rear foot compared with standard HHSs [5]. In addition, revised HHSs are preferable to standard HHSs because they result of normal improvement of foot pressure and a positive point of static balance [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although excessive load on the forefoot and joint positioning of the lower extremities could return to normal without wearing HHSs, habitual wearing of HHSs may fixate abnormal postural alignment with shortened calf muscles and a tight Achilles tendon [3]. In addition, tibialis anterior (TA), quadriceps, and gastrocnemius muscles demonstrate increased electromyographic (EMG) activity with raised heel height, there were potentially contributed to instability of ankle joint [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations